An Overview of the CY 2019 Home Health Prospective Payment System Rate Update for Medicare Programs - Rivera Jr., Gonzalo; Holt, Paul (Journal of Management Policy and Practice, 2019)
The purpose of this paper is to discuss an overview of the new updated Medicare HH PPS rates for CY 2019. For Medicare covered home health services beginning January 1, 2019, this proposed rule titled “Medicare and Medicaid Programs: CY 2019 Home Health Prospective Payment System Rate Update” discusses the new changes for the HHPPS payment rates. This proposed CY 2019 rule includes the proposed current changes to the 60-day episode payment rates, the national per-visit rates, the nonroutine medical supplies (NRS) conversion factor, and case-mix weights.